2020
DOI: 10.1002/cncr.33305
|View full text |Cite
|
Sign up to set email alerts
|

Germline genetic testing in breast cancer: Rationale for the testing of all women diagnosed by the age of 60 years and for risk‐based testing of those older than 60 years

Abstract: Approximately 5% to 10% of women diagnosed with breast cancer will have a pathogenic variant (PV) in a hereditary cancer susceptibility gene, and this has significant implications for the management of these patients and their relatives. Despite the benefits of genetic testing, many eligible patients with breast cancer never undergo testing because of various barriers, including complicated testing criteria such as those from the National Comprehensive Cancer Network (NCCN). In 2019, the American Society of Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 27 publications
4
32
0
Order By: Relevance
“…The recent prospective, multisite Interrogating Cancer Etiology using Proactive genetic Testing (INTERCEPT) study found that clinicians caring for 42 (28.2%) of 149 patients with high-penetrance PGVs documented modifications to treatment and medical management as a result of the findings. 2 These findings are also supported by other studies that have explored individual cancer types more deeply, including breast, 4 , 50 , 59 , 61 , 62 , 70 colorectal, 63 , 65 pancreatic, 19 gastrointestinal, 20 prostate, 71 and other urogenital cancers. 27 , 28 , 68 …”
supporting
confidence: 74%
“…The recent prospective, multisite Interrogating Cancer Etiology using Proactive genetic Testing (INTERCEPT) study found that clinicians caring for 42 (28.2%) of 149 patients with high-penetrance PGVs documented modifications to treatment and medical management as a result of the findings. 2 These findings are also supported by other studies that have explored individual cancer types more deeply, including breast, 4 , 50 , 59 , 61 , 62 , 70 colorectal, 63 , 65 pancreatic, 19 gastrointestinal, 20 prostate, 71 and other urogenital cancers. 27 , 28 , 68 …”
supporting
confidence: 74%
“…Genetic testing, supported by advancement in genetic sequencing techniques and bioinformatics tools, allows the efficient detection of germline mutations in breast cancer patients. Genetic testing in breast cancer has substantial implications for cancer prevention, early detection, and treatment for patients and their relatives ( Table 2 ) [ 149 ]. Since the last three decades, the germline genetic testing for inherited breast cancer risk prediction has evolved substantially [ 150 ].…”
Section: Different Available Approaches To Control Breast Cancermentioning
confidence: 99%
“…In 2019, the American Society of Breast Surgeons (ASBrS) proposed germline genetic testing for all breast cancer patients to increase the identification of pathological variant carriers [ 168 ]. Over the guidelines of the NCCN (National Comprehensive Cancer Network) and ASBrS, a Mayo Clinic study in 2020 proposed a hybrid approach for germ genetic testing for all diagnosed breast cancer patients with 65 years age using the NCCN criteria for older patients [ 149 ]. Keeping ≤60 or ≤65 years of age for universal testing has detected more pathological variants (11.9% and 15.7% respectively) in comparison with using the NCCN criteria [ 169 ].…”
Section: Different Available Approaches To Control Breast Cancermentioning
confidence: 99%
“…A subsequent analysis demonstrated that by lowering the age at diagnosis for universal testing to 60 years, results were essentially identical but an additional 10% of patients were spared genetic testing. 22 In the article that accompanies this editorial, Boddicker et al 23 provide data that support genetic testing for women diagnosed with early-stage TNBC at any age. They found that the frequency of BRCA1/2 or PALB2 mutations in women with TNBC diagnosed after age 65 years is 3.0%, using population-based studies within the CAnceR RIsk Estimates Related to Susceptibility (CARRIERS) consortium.…”
mentioning
confidence: 99%